Excavation of a Bronze Age funerary site at Loth Road, Sanday, Orkney - Sharman, Paul M; Alldritt, Diane; Clarke, Ann; MacSween, Ann; Photos-Jones, Effie; Roberts, Julie (Scottish Archaeological Internet Reports, 2007)
Excavations in 1991 beside Loth Road, Sanday (NGR: HY 60553 34489), revealed a funerary site, including two cists, which contained cremated human bone, and several pits. The cremation burial in one of the cists was contained in a soapstone vessel. These features presented evidence for the sorting, selection and differential deposition of pyre remains. The cists and pits were surmounted by a kerbed cairn of unusual construction. Radiocarbon dates from the pits placed the site in the Early to Middle Bronze Age.